Clinical Effect of Application of Interventional Treatment Models for Improvement of Quality of Postoperative Recovery in Elderly Patients with Total Hip Arthroplasty - Shen JL; Hang LY; He F; Xu X; Sun HP (International Journal of General Medicine, 2022)
Jia-Li Shen, Ling-Yan Hang, Fan He, Xiao Xu, Hui-Ping Sun Department of Orthopaedic, Affiliated Hangzhou First People’s Hospital, Zhejiang University School of Medicine, Hangzhou, 310006, People’s Republic of ChinaCorrespondence: Jia-Li Shen, Department of Orthopaedic, Affiliated Hangzhou First People’s Hospital, Zhejiang University School of Medicine, No. 261 Huansha Road, Shangcheng District, Hangzhou, 310006, People’s Republic of China, Email 13857169118@163.comObjective: To investigate the application value of the interventional treatment model for improving the recovery of elderly patients after total hip arthroplasty (THA).Methods: A total of 50 patients who received THA were randomly divided into the control group (25 cases) undergoing traditional treatment and the experimental group (25 cases) undergoing intervention of cognition, emotion, environment, education, nutrition, and sleep. The mini-mental state examination (MMSE) score, the incidence and duration of postoperative cognitive dysfunction (POCD), the out-of-bed activity time, hospital stays, and the satisfaction degree of patients were compared between the two groups.Results: There was no statistically significant difference in basic information between the two groups. On days 7 and 14 after surgery, the MMSE score of the control group was significantly lower than that of the experimental group (P < 0.05). The incidence of POCD in the experimental group was lower and its duration was shorter than in the control group but without statistical significance. Besides, the significantly decreased out-of-bed activity time, the reduced length of hospital stay, and the higher satisfaction degree were observed in the experimental group (P < 0.05).Conclusion: Interventional treatment model could significantly increase the MMSE score, accelerate the recovery of elderly patients after THA, and increase their satisfaction degree.Keywords: interventional treatment model, postoperative cognitive dysfunction, postoperative recovery, total hip arthroplasty, elderly patients